Southeast Asia : the long road ahead - Lim, Chong-Yah (World Scientific, 2009)
Southeast Asia: The Long Road Ahead is a serious and concise study on various important economic aspects of Southeast Asia. Existing economic studies on the region are mainly topical in nature. Most of the publications only attempt to offer a partial treatment of the issues and fail to examine these issues in a holistic manner. The objective of this book is to provide a more complete cross-country discussion on the economic issues and problems facing Southeast Asia. Besides critically examining the multiple facets of changes and problems that have been and will be encountered by Southeast Asia, the book also presents a lucid exposition on the prospects of the region. However, it does not stop there. It moves on to provide pointers and suggestions on how Southeast Asian countries should proceed with their development options and processes. The book should be of interest to economists, graduate students on Southeast Asia and all those who want to have a better knowledge and understanding of the important Southeast Asian region. (Publisher)